Frozen Tilapia Fillets Business Process Analysis Using Integration Definition for Function Modelling - Sintia Putri Pradita; Nindya Laksita Laras (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2022)
Aquaculture products in Indonesia have great potential in line with population growth. The demand for frozen tilapia fillets is increasing both in Indonesia and globally. Our objectives are to identify the current business process activities of a frozen tilapia fillet product, analyse problems and provide improvement strategies. In-depth interviews and observations were conducted with stakeholders. The business processes were analyzed using an Integration Definition for Function Modelling (IDEF0) to identify the activities and problems at the organizational level, the production plant level and the production department level. The results at the production plant level showed that there was a lack of strategic forecasting and inventory management in the planning activity. In the sourcing activity, the limited number of suppliers and inconsistent fish quality were the main problems. The lack of implementation of a good material handling and production system was a concern in the making activity. The problem in the delivering activity was the lack of product tracking which results in product returns due to defects. The researchers' recommendations, based on several literature reviews, are expected to improve the supply chain of frozen tilapia fillets in Yogyakarta and Central Java to increase its competitive advantage.